Outcomes and Hand Use of Reaching Attempts: Comparison of Infants at Risk for Developmental Disability and Infants With Typical Development - Remec, Nushka; Zhou, Judy; Shida-Tokeshi, Joanne; Pickering, Trevor A.; Vanderbilt, Douglas L.; Smith, Beth A. (Frontiers in Psychology, 2022)
Background: Infants at risk for developmental disabilities often show signs of motor delay. Reaching is a skill that can help us identify atypical motor trajectories in early infancy. Researchers have studied performance after onset of reaching, but none have followed infants at risk from pre-reaching to skilled reaching. Aims: We assessed differences in reaching outcomes and hand use as reaching skill emerged in infants at risk for developmental disabilities and with typical development. Methods and Procedures: We followed infants at risk for developmental disabilities (n=11) and infants with typical development (n=21) longitudinally as they developed reaching skill. Infants reached for a toy at midline while sitting in the caregiver’s lap. Video data were coded for reach outcome (miss, touch, partial grasp, whole-hand grasp) and hand use (right, left, bilateral). Outcomes and Results: Infants at risk had a larger proportion of missed reaches across visits compared to infants with typical development. Infants at risk also showed less variability in hand use when grasping over the study period. Conclusions and Implications: Our results provide information to support early differences in reaching performance to inform identification of typical and atypical developmental trajectories. Future studies should assess how the missed reaches are different and consider other quantitative measures of movement variability in infants at risk.